Arti Penting Pengendalian Diri dalam Islam: Studi Kritik Hadis - Muhammad Aufa Alfaiz; Dian Siti Nurjanah; Husnul Qodim (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about self-control. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about self-control in the history of Ahmad No. 10284. The results and discussion of this study indicate that the status of the hadith is authentic with the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Ahmad No. 10284 is relevant to be used as a spirit in an effort to increase self-control.